2014
DOI: 10.1007/s00535-013-0929-4
|View full text |Cite
|
Sign up to set email alerts
|

Immune-epithelial crosstalk at the intestinal surface

Abstract: The intestinal tract is one of the most complex organs of the human body. It has to exercise various functions including food and water absorption, as well as barrier and immune regulation. These functions affect not only the gut itself, but influence the overall health of the organism. Diseases involving the gastrointestinal tract such as inflammatory bowel disease and colorectal cancer therefore severely affect the patient's quality of life and can become life-threatening. Intestinal epithelial cells (IECs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 127 publications
0
47
0
1
Order By: Relevance
“…Recent approaches focus on mechanistic modeling of the transport and disposition kinetics of chemical compounds in multilayered skin at the cellular level (Dancik et al, 2013;Kasting et al, 2013; secretion of mucins that form an additional protective barrier), Paneth cells (secretion of antimicrobial peptides) and entero-endocrine cells (secretion of hormones regulating motility and release of digestive enzymes). Other important cell types present are involved in antigen processing and mucosal immunity, for example intraepithelial lymphocytes and microfold (M) cells, which transport organisms and particles from the gut lumen across the epithelial barrier to immune cells (Kucharzik et al, 2000;Wittkopf et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Recent approaches focus on mechanistic modeling of the transport and disposition kinetics of chemical compounds in multilayered skin at the cellular level (Dancik et al, 2013;Kasting et al, 2013; secretion of mucins that form an additional protective barrier), Paneth cells (secretion of antimicrobial peptides) and entero-endocrine cells (secretion of hormones regulating motility and release of digestive enzymes). Other important cell types present are involved in antigen processing and mucosal immunity, for example intraepithelial lymphocytes and microfold (M) cells, which transport organisms and particles from the gut lumen across the epithelial barrier to immune cells (Kucharzik et al, 2000;Wittkopf et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Given that IL-10 inhibits IFN-induced genes by suppressing the tyrosine phosphorylation of STAT-1 [26,33], we investigated the expression of STAT-1 and p-STAT-1 in vivo and in vitro. Interestingly, we found that C-BF increased the phosphorylation of STAT-1 in the jejunum of weanling piglets compared to the control treatment.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 is a potent immunosuppressive molecule that mediates the down-regulation of Th1 responses by inhibiting the production of proinflammatory cytokines. The crucial role of IL-10 in the intestine was established based on the finding that IL-10-deficient mice spontaneously developed enterocolitis [26,[30][31][32]. In addition, IL-10 inhibits NF-κB activation in human monocytes [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal epithelial cells are uniquely located at the border of luminal commensal microbiota and the lamina propria of the intestine [30,31] . Secretory intestinal epithelial cells can secrete mucins and antimicrobial proteins to establish a physical and biochemical barrier between the bacterial and epithelial surfaces [22,30] .…”
Section: Discussionmentioning
confidence: 99%